The Impact of the Arbuscular Mycorrhizal Fungi on Growth and Physiological Parameters of Cowpea Plants Grown under Salt Stress Conditions - Abdel-Fattah, Gamal M.; Rabie, G. Hassan; Lamis, D. Shaaban; Rabab, A. Metwally (International Journal of Applied Sciences and Biotechnology, 2016)
A pot experiment was conducted to examine the effects of arbuscular mycorrhizal fungi on growth, nutrition and some physiological aspects of cowpea (Vigna unguiculata L.) plants grown at different salinity concentrations (0, 10, 15, 20, 25 and 30 mM NaCl). Under saline condition, arbuscular mycorrhizal fungal (AMF) inoculation significantly increased growth responses, photosynthetic pigments, nutrient contents, proline and total soluble protein of cowpea plants compared to non-AM ones. Those stimulations were related to the levels of mycorrhizal colonization in the associated plants. Interestingly, high proline, chlorophyll content and antioxidant enzymes in AM plants could be important for salt alleviation in plants growing in saline soils. Int J Appl Sci Biotechnol, Vol 4(3): 372-379